Preventive behaviors among Malaysian parents towards hand, foot, and mouth diseases using health belief model - Rajamoorthy, Yogambigai; Mohd Taib, Niazlin; Harapan, Harapan; Luther Wagner, Abram; Aye Aye, Khin; Munusamy, Subramaniam (IIUM Press, 2022)
INTRODUCTION: Hand, foot mouth disease (HFMD) is caused by a virus and commonly affects children five years or below. However, the determinants of the associated factors with preventive behaviour among parents are still lacking. This study aims to assess the range of preventive behaviour towards HFMD among parents in Selangor, Malaysia. MATERIALS AND METHODS: A cross-sectional survey was conducted using a convenient sampling method. The associations between independent variables and preventive behaviours were assessed with multivariate regressions. RESULTS: In total, 556 parents completed the survey. The majority of the parents had good preventive behaviours towards HFMD. Age, gender, income, perceived susceptibility, and perceived benefit were associated with preventive behaviour. CONCLUSION: Although, the preventive behaviour of HFMD among parents is crucial, however, it is influenced by parents' perceptions. The strategies to enhance the parent’s perception are needed to increase the preventive behaviour towards HFMD infection.